Provider Exclusion in US Private Health Insurance Contract - Costello, Michael M (Archives of Business Research, 2024)
Two national newspaper articles published in the Fall of 2018 addressed the issue of private health insurance provider contracts that act to exclude specific health systems from health plan networks. Inevitably, the question arises: Are such agreements illegal restraints of trade actionable under federal and state antitrust laws? A long-standing tenet of antifrust law is that it exists to protect competition not competitors. Excluding providers may be a legitimate outgrowth of the contracting process and therefore legal. However, an examination of the contracting process may reveal anticompetitive intent to restrain trade. The specific facts surrounding provider exclusion must be analyzed carefully in an effort to determine if there is illegal restraint of trade.